Sustainable electrochemical energy generation using ultrathin nanoflakes of mixed phase CoMnMoS as a robust electrocatalyst - Salunke, Amol S.; Patil, Ruturaj P.; Shrestha, Nabeen K.; Cho, Sangeun; Im, Hyunsik; Inamdar, Akbar I. (Journal of power sources, 2025)
Hydrogen evolution reaction (HER) electrocatalysts based on non-precious metals have been the subject of research across a broad pH range due to the growing demand for efficient and economical water-splitting devices. To do so, ternary metal sulfides have been utilized as an efficient HER electrocatalyst because of their excellent physical, chemical properties and semiconducting characteristics. Therefor in this work we studied transition metal (Co)-decorated ternary metal sulfides (MnMoS) on Nickel foam for HER activity. The MnMoS catalysts are synthesized using hydrothermal technique followed by Co-decoration via electrodeposition. It shows superior electrochemical properties such as low HER overpotentials of 91 mV at a current density of 10 mA cm−2 in alkaline media, a Tafel slope of 105.6 mV dec−1. Moreover, Co-MnMOS exhibited remarkable electrochemical stability for over 100 h, under a high current density of 1000 mA cm−2. The overall water splitting (OWS) activity of the electrolyzer fabricated with benchmark RuO2 at the anode and the Co-MnMoS at the cathode demonstrated exceptionally low potential of the 1.52 V to achieve a current density of the 10-mA cm−2 with a Faradaic efficiency of 95 %. Moreover, it is highly durable and active in alkaline solution even at high current density of the 800-mA cm−2 demonstrating its promising candidature for green hydrogen technology. [Display omitted] •Cobalt-decorated MnMoS catalysts are fabricated via hydrothermal technique.•Co-MnMoS catalysts were utilized for overall water splitting activity.•It exhibits excellent HER (91 mV) at 10 mA cm−2 and Tafel slope of 105.6 mV dec−1.•Industrial relevant current density of 1000 mA cm−2 is achieved.•The electrolyzer showed high electrochemical durability for more than 100 h.